Acesso a mercados e luta por reconhecimento na construção do Selo Quilombos do Maranhão - Vieira, Lucas Moretz-Sohn David (2023)
In contemporary contexts, in which sociopolitical, environmental, territorial, and identity values have become strategic in the social construction of markets, initiatives to create recognition mechanisms have become extremely relevant. On one hand, we have the notion of recognition that refers to the idea of recognizing a certain product by contingents of consumers, especially in relation to the form and place where they are produced, a notion that is more recurrent in academic world. On the other hand, the idea of recognizing a human being by his way of life and historical trajectory of his social identity, considering markets as arenas of "figths for recognition", an approach proposed by Axel Honneth and used in this research. In this sense, we analyze the case of the creation of the Selo Quilombos do Maranhão, in the historical trajectory and context that led to the implementation of the main public policies for Brazilian Quilombola communities, its relations with the institutionalization of the Selo Quilombos do Brasil and its implications for the notions of recognition devices, market access, and figths for recognition. The methodology of this research was qualitative, resorting to bibliographic research, document analysis, direct observation, semi-structured interviews, open interviews, meetings with community groups; besides the attendance and establishing livestreams, with the participation of people involved in the creation or implementation of the Selos Quilombos do Brasil and Quilombos do Maranhão. The interviews were carried out with government representatives, leaderships of quilombola social movements, and with representatives of the Quilombola communities, all from the state of Maranhão. The Quilombola communities where the field work took place were Pedrinhas, in Itapecuru-Mirim/MA; Jiquiri, in Santa Rita/MA; Cantinho and Santo Antônio, in Barreirinhas/MA. In the light of Honneth's approach, we conclude that the Selo Quilombos do Maranhão was not directly important for the "figths for recognition" or for the access to markets by the quilombola communities involved. However, we ponder that the creation of this device is part of the historical process of figths of these communities, whose identities were being built in line with public intervention. Moreover, the expansion of the circulation and consumption of these ethnocultural products has the potential to promote antiracist practices and socio-productive inclusion of Quilombola communities, contributing to the recognition of these social subjects historically marginalized in Brazilian society.